Motivation in learning to read - Thomsen, Dorothy
There is no one proven way or one superior method to motivate the learning of reading. This vital part of teaching poses a constant challenge to teacher and student. Many different ideas to encourage the student to learn can be developed by putting to work the different theories of motivation, especially the cognitive theory.
Keywords: Motivation (Psychology).; Reading interests